Epidemiological assessment of the peculiarities of the development of non-tumor diseases residents of the radioactively contaminated areas aged 18-47 years old, born before the Chernobyl accident. The observation period 1988-2016 - Zh. Yaroshenko; K. Prykashchykova (Kazimierz Wielki University, 2020)
An epidemiological assessment of changes in the health status of RCA residents under 18 years old at the time of theChernobylaccident for the period 1988-2016 was conducted. The main source of information was the database of medical data of the State Register of Ukraine (SRU) of victims of theChernobylaccident. The cohort consisted of 33,684 residents of RCA aged 18 to 47 years old (as of the date of theChernobylaccident under the age of 18), of whom men - 16,757, women - 16,927. The state of health of the offspring was assessed based on the information from the Ukraine State Register (USR). 45417 cases (100%) of non-tumoral diseases were identified in eight classes of ICD-10, which is 103.46 ± 0.46 cases per 1000 person-years of follow-up. 21,148 diseases were diagnosed in men (96.32 ± 0.63 per 1000 person-years), and24,269 inwomen (110.60 ± 0.67). Epidemiological analysis of non-tumoral morbidity and disability was conducted over five-year observation periods: 1988-1992, 1993-1997, 1998-2002, 2003-2007, 2008-2012, and 2013-2016. The dynamics of non-tumoral morbidity of the subjects show a gradual decrease in morbidity from the highest in the first period (the first six years after the accident) to the lowest in the last period (2013-2016). Thyroid diseases (97.60%) are the main component among the nosological forms of the endocrine system, eating disorders and metabolic disorders (18.97 ± 0.20 cases per 1000 man-years) of the total number for 1988-2016 epidemiological observation. In the structure of the causes of disability, the largest components are diseases of the nervous system and mental and behavioral disorders, which together account for 51.75%. According to the indicators of the structure, the residents born before the Chernobyl accident (April 26, 1986) aged 0 to 18 years, showed the highest incidence of non-tumoral diseases of the respiratory, digestive, endocrine system (almost 80%). Men (1.1-1.4 times) were more likely to suffer from diseases of the respiratory system, digestive system, circulatory system, musculoskeletal system, mental and behavioral disorders. In women, the incidence of non-tumoral diseases was higher (1.1-3.4 times) in the endocrine, nervous and genitourinary systems. Against the background of a gradual decrease in the incidence from the first to the last five-year observation period, there is an increase in the disability of the subjects in the three disability groups; thus, there was synchronization in different directions.